Kajian tentang identiti orang Cina di Malaysia dari segi epistemologi : Ulasan - Lee, Yok Fee (Universiti Kebangsaan Malaysia, 2009)
Ethnic study is gaining importance in plural societies, including Malaysia, in their earnest effort in developing national unity and integration. How the Chinese in Malaysia identify themselves has great impact on the issue of national unity in Malaysia given the large number of them in terms of population in the country. Since the 1980s, many studies on Malaysian Chinese identity have been conducted. This paper aims to review these writings by examining their epistemology and methodology which categorise them according to the nature of knowledge. Majority of the writings analysed changes and the formation of Chinese identity based on social development in Malaysia. From them, two major categories have been identified as the “author-oriented” and “actororiented” types of knowledge